Body composition and chemotherapy toxicity in women with early breast cancer (CANDO-3): protocol for an observational cohort study. Issue 2 (22nd February 2022) - Durkin, Kesta; Heetun, Adam; Ewings, Sean; Munday, Richard; Wootton, Stephen A; Turner, Lesley; Copson, Ellen R; ,; Cutress, Ramsey I
Abstract : Introduction: Systemic anticancer therapy is given to selected patients with early breast cancer (EBC) before or after surgery with the aim of eradicating micrometastatic spread and reducing the risk of cancer recurrence. Chemotherapy treatment is most effective when patients receive the optimum dose, on time and without delays or reductions in their treatment doses. Most chemotherapy drugs are dosed according to body surface area calculated from a patient's height and weight. These calculations were however designed based on data from normal weight patients. This has resulted in uncertainty as to the optimal dosing for patients with different amounts of blood, muscle and fatty tissue (body composition). This study uses segmental bioelectrical impedance analysis (using the Seca mBCA 515) to determine whether differences in the measures of resistance and reactance, and derived estimates of body composition, are predictive of chemotherapy toxicity in the treatment of EBC. Methods and analysis: A prospective observational cohort study of women with EBC in whom adjuvant or neoadjuvant chemotherapy is planned. A total of 300 participants will be recruited across nine UK hospital sites. The primary outcome is to determine if higher fat mass index is associated with increased National Cancer Institute Common Terminology Criteria for Adverse Events v5.0 grade 3 (or higher) chemotherapy toxicity. Ethics and dissemination: This study has received ethical approval from the South Central Hampshire B Research Ethics Committee, England (19/SC/0596: IRAS: 263666). The chief investigator and coinvestigators will be responsible for publication of the study findings in a peer-reviewed journal, on behalf of all collaborators. Trial registration number: ISRCTN79577461 .